A novel authentication and key‐agreement scheme for satellite communication network - Altaf, Izwa; Arslan Akram, Muhammad; Mahmood, Khalid; kumari, Saru; Xiong, Hu; Khurram Khan, Muhammad (Transactions on emerging telecommunications technologies, 2021)
Summary In these days, satellite communication networks are playing a significant role in facilitating the crucial infrastructural services that include environmental monitoring, electronic surveillance, public safety, intelligence operations for law enforcement, government agencies, and the military. However, security researchers have uncovered that many protocols for these satellite communication networks have some vulnerabilities and flaws that can allow remote attackers to intercept, block, and manipulate critical communication over the network. Therefore, in this article, we introduce an efficient and simple authentication key agreement protocol for securing mobile satellite communication systems. Our proposed protocol resists against denial of service, smart‐card stolen, replay, user impersonation, and stolen verifier attack. Furthermore, our protocol provides various functionality features like perfect‐forward secrecy, mutual‐authentication, dynamic identity, and session‐key agreement. Moreover, the performance analysis of our protocol shows that the communication and computation cost of the proposed protocol is far less than the existing protocols. Hence, our proposed protocol offers simple, efficient, secure authentication, and key agreement for mobile satellite systems. Design of lightweight key agreement protocol for Satellite Communication System. The protocol protects the userŠs real identity from adversary. Security strength of our protocol against serious attacks is verified through formal analysis. Performance comparison and security analysis confirm that our protocol has an upper edge in terms of security strength and performance efficiency over related protocols.